VALUES OF CHARACTER EDUCATION IN THE WEDDING SAPRAHAN TRADITION IN THE VILLAGE OF LELA, TELUK KERAMAT DISTRICT, SAMBAS REGENCY - Yafi, Reyhan Ainun; Kumalasari, Dyah; Irawan, Ria; Firmansyah, Haris; Arifiyanti, Fitria (Jurnal Pendidikan Sosiologi dan Humaniora, 2023)
This research examines the values of character education of the people of Lela Village in the tradition of marriage saprahan. The Malay community owns the saprahan tradition, which is still maintained. This study aims to analyze whether the saprahan tradition in Lela Village contains character education values and is a factor in preserving the tradition. The method used in this study is descriptive qualitative with an ethnographic approach. The sources used were interviews with community leaders, traditional leaders, and youth of Lela Village. The results showed that the implementation of the marriage saprahan tradition there are several values of character education in the marriage saprahan tradition, including religious values with the indication of the philosophy of the number of tools and people involved. Second, the creative value seen from the use of modern tools rather than traditional tools because they are already scarce. Third, democratic values demonstrated through the deliberations of local communities. Fourth, the communicative value that can be seen from the way the owner is happy to gather the community. Fifth, the value of social care can be seen from the involvement of youth and ethnicities other than Malays by attending invitations. And sixth, the value of responsibility is seen from the division of labor given to each implementing committee. However, the community needs to pay attention to regeneration to continue to be able to preserve the tradition of wedding ceremony in Lela Village, Teluk Keramat District, Sambas Regency.